Efeitos da reabilita????o pulmonar associada ?? fisioterapia respirat??ria vs fisioterapia respirat??ria na capacidade f??sica, for??a muscular perif??rica e qualidade de vida em pacientes com bronquiectasia: ensaio cl??nico randomizado e controlado - Camargo, Anderson Alves de (2015)
Introduction: There is a shortage of studies evaluating the effects of respiratory physiotherapy isolated and linked to pulmonary rehabilitation in adults with bronchiectasis (BCT), and inflammatory level comparison of these patients with a control group. Aim: Study 1: To correlate the inflammatory and oxidative stress state with lung function and physical capacity, and with basal physical capacity after a pulmonary rehabilitation program associated with the respiratory physiotherapy; and Study 2: To compare the effects of a pulmonary rehabilitation program associated to respiratory physiotherapy with respiratory physiotherapy singly in physical capacity, peripheral muscle function and quality of life in patients with bronchiectasis. Methods: In the first study, 74 patients and 29 controls performed cardiopulmonary exercise test on cycle ergometer (CPET) and incremental shuttle walking test (ISWT), in addition to the assessment of the total number of steps/day (NSD) and the Pro and anti-inflammatory mediators and Pro and anti-oxidants in plasma. In the second study, 82 patients were randomized into two groups: respiratory physiotherapy (RP) and RP associated to pulmonary rehabilitation (RP+PR). Patients performed the ISWT and SWT endurance (ESWT), the maximum and submaximal CPET (sub), test of strength for the biceps brachii (BB), medium deltoids (MD) and quadriceps femoris (QF) and responded to the St. George's Respiratory Questionnaire (SGRQ) for assessment of health-related quality of life (HRQOL). NSD was obtained by pedometer and dyspnoea was measured by the Medical Research Council (MRC). Results: Study 1 ??? The level of cytokines IL1-?? and IL-6 was significantly higher compared to the control group, but for Pro markers and antioxidants no differences were found. There was significant negative correlation of VO2 with IL1-?? (r: -0.42), IL-6 (r: -0.31), thiobarbituric acid (T-BARS, r: 0.30), Carbonyl (r: -0.39) and nitrite (r: 0.32). The ISWT correlated with Catalase (r: 0.25) and total antioxidant capacity (TRAP, r: 0.23). Study 2 ??? Comparing the pre-and post-intervention intra-group effects, there was significant increase in ISWT, ESWT, CPET load, and muscle strength of DM and BB for the RP+PR group, while the endurance time in CPETsub increased both in RP+PR and RP groups; there was improvement for the RP group in all domains of SGRQ, while the RP+PR group only improved in symptoms. When comparing the effects of treatment in both groups (RP vs RP+PR), there was no statistically significant difference for any of the outcomes studied. Conclusion: Study 1 ??? Patients with BCT presented high systemic inflammation even in the stable phase of the disease, with equivalent Pro markers and antioxidants compared to the control group. Oxidative and inflammatory markers correlate with the aerobic and functional capacity. Study 2 ??? Although there was increasing exercise tolerance only at the RP+PR group, both groups showed improvement in HRQOL. Even though there wasn???t difference between interventions, it is preferable to associate RP to PR, because the latter promoted significant benefits in peripheral muscle strength and physical ability.